RCAM: a proposed model of recovery capital for adolescents. (3rd September 2019) - Hennessy, Emily A.; Cristello, Julie V.; Kelly, John F.
Abstract: Problematic substance use is a challenge worldwide among adolescents. The recovery process requires holistic support addressing multiple and intersecting substance use risk factors; yet, there remains a lack of evidence on how to best understand and support adolescents in recovery. Recovery capital (RC) is a model that can be used to identify areas of assets that could be enhanced and barriers to address in one's recovery process; however, this construct was generated through a study of adults who achieved natural recovery and it has since been used to frame adult recovery-related literature across the world. The primary aim of this article is to outline the rationale for and present a Recovery Capital for Adolescents Model (RCAM). The article will discuss the original recovery capital model, describe adolescent development, substance use, and recovery, and detail proposed developmental adaptations. Future qualitative and quantitative research should explore the RCAM to assess whether the proposed dimensions are complete as well as to assess its utility in clinical settings for identifying strengths and barriers for adolescents in or seeking recovery.